Challenges faced by teachers in implementing inclusive education at Mgoqo primary school at early childhood level - Dube, Rosina S. (Midlands State University, 2019)
A number of researchers have undertaken some study in line with the challenges faced by teachers in implementing inclusive education at Mgoqo Primary School level in Zimbabwe and beyond. It is however, notable with regret that the challenges faced by Early Childhood Education teachers in implementing inclusive education have not been fully examined and incorporated in the previous studies, while the issue and impact of the new curriculum (2015-2022) were not considered in most of the researches. It is within this framework that this study partook to investigate challenges faced by teaching in implementing inclusive education at ECE level at Mgoqo School in Bulawayo. The research was conducted in Bulawayo at Mgoqo Primary School. A population of sixty which comprised twenty-four ECE teachers, twenty ECE disabled learners and twenty parents of disabled learners, from which a total of twenty participants were selected to represent the population. Among the respondents were ten teachers, five ECE disabled learners and five parents of disabled learners. This was done this way for easy access when gathering information. The researcher gathered a convenient sample where more convenient teachers, learners and parents were chosen from the population. The researcher employed the purposive sampling technique where information rich respondents were selected for in-depth study. The sample size was twenty consisting of ten teachers, five ECE disabled learners and five parents of disabled learners. The research followed both the qualitative and quantitative approaches since data gathered was both descriptive and numerical. The researcher used case study design. Questionnaires were distributed to the teachers and interviews conducted to parents and teachers to gather as much information as possible and also to check if their response correlate to each other’s. Observations were also conducted to view the classrooms where those disabled learners are taught and also to observe how the teachers teach the disabled learners. The literature review gathered by the researcher presented views by various authors on the challenges faced by teachers in implementing inclusive education worldwide. This literature helped the researcher to have an insight into the inclusive education and its challenges when implemented or being implemented. Data was presented in three different ways namely tables, bar graphs and pie charts. The research found that teachers, parents and ECE disabled learners face different challenges in the implementation of inclusive education at Mgoqo Primary School in Bulawayo. The challenges were lack of parental involvement, lack of resources and lack of professional qualifications among others. As a result, it was recommended that the ministry should design a thorough and clear educator skills development plan programme in disability and inclusive education in teachers’ colleges and on the part of educators who are already serving in the mainstream schools. The Ministry should also unveil sponsorship packages for teacher capacity development schemes to enable all teachers to gain full conscience on inclusivity in education. Finally, schools and their responsible authorities were encouraged to ensure that they make their environments friendly to all learners through infrastructural development programs, resource resuscitation plans and involving the parents’ body in developmental issues.